The use of sulphate-calcium solid waste in resourcesaving production of building materials and alternative products - Fedorchuk Yu. M. Yuri Mitrofanovich; Matvienko V. V.; Naryzhny D. V.; Volkov A. A.; Malinnikova T. P.; Klemesh J. J.; Varbanov P.; Anikanova L. A.; Sadenova M. A.; Zamyatin N. V.; Smirnov G. V. (Энергосбережение и повышение энергетической эффективности в строительстве и коммунальном хозяйстве, 2018)
Заглавие с экрана